A Longitudinal Investigation Into Marital Quality as a Mediator Linking Childhood Abuse to Affective Symptoms. (27th May 2021) - Fitzgerald, Michael; Berthiaume, Kelly
Abstract: Objective: Childhood abuse is positively associated with adult mental health problems and adult interpersonal relationships have been previously suggested to be a mediator. The role of marital partners, however, is less well understood. The current study will investigate marital quality as a mediator linking childhood abuse and positive and negative affective symptoms. Method: The current study utilized 3 waves of data from the Midlife Development in the United States. Using a sample of 1, 104 married adults (95.4% White), structural equation modeling examined the mediating effect of marital quality linking childhood abuse to positive and negative affective symptoms over a 20-year period. Results: Structural equation modeling revealed that childhood abuse was inversely associated with marital quality but was not directly associated with positive or negative affective symptoms. Marital quality was positively associated with greater positive affect and negatively associated with lower negative affect over a 9-year period, controlling for prior symptoms. Tests of indirect effects indicate that marital quality mediated the relationship between childhood abuse to both positive and negative affective symptoms, fully accounting for the association. Discussion: It appears that childhood abuse impacts the quality of adults' marriages, which may have significant implications for both positive and negative aspects of adult mental health. Marriages may be an important factor in understanding mental health in midlife and older adults among adults who were abused. Interventions should target the quality of adult marriages, and focusing on marital support, strain, and disagreement may be particularly effective.